THE IMPACT OF COMPLEMENTARY FEEDING TYPE ON THE NUTRITION STATUS OF INFANTS 6 TO 12 MONTHS OF AGE IN SUBURBAN SEMARANG INDONESIA - Suyatno, Suyatno (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: After 6 months, baby must be given complementary feeding. Many considerations behind the choice of the family on both types of weaning food, one of which is related to the impact of these foods on nutritional status and infants healthy. Malnutrition increases as a result of complementary feeding are given to infants is not right, either type or quantity. Aims: The research objective was to determine the commercial and local food practices in sub- urban areas, and determine the reason and analyze the impact of both types of weaning food on the nutritional status of infants 6-12 months. Methods: This study was an observational study with a cross-sectional design. Location of research was in the work area of Kedungmundu Health Center, Semarang City Indonesia. The research samples were families with babies aged 6-12 months. A number of samples 94, selected by random. This type of analysis used was a different test. Results: The results showed 55.3% of infants were fed with local weaning food, the rest were kind of commercial food. Almost all babies had been given a weaning food in less than 6 months, both derived from the type of local or commercial food. Families closed the type of commercial food, because this type was more practical, while the local food (homemade) chosen because it was more natural, safer and more economical. There were no differences in nutritional status among infants 6-12 months who had complementary feeding practices with commercial and local food. Conclusion: It was concluded, infant complementary feeding practice with infant commercial and local food did not have a different impact on the nutritional status in infants 6-12 months.Â